The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1080/10937400701724303
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of a Bisphenol a Oral Reference Dose (RfD) and Drinking-Water Equivalent Concentration∗

Abstract: Human exposure to bisphenol A (BPA) is due to that found in the diet, and BPA and its metabolites were detected at parts per billion (or less) concentrations in human urine, milk, saliva, serum, plasma, ovarian follicular fluid, and amniotic fluid. Adverse health effects in mice and rats may be induced after parenteral injection or after massive oral doses. Controlled ingestion trials in healthy adult volunteers with 5 mg d16-BPA were unable to detect parent BPA in plasma despite exquisitely sensitive (limit o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
97
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(104 citation statements)
references
References 365 publications
(530 reference statements)
6
97
1
Order By: Relevance
“…The relatively few regulatory testing guidelines of large multigeneration reproductive toxicology studies are under governmental guidelines and GLPs, with oral routes of administration, a larger number of groups (minimum 4), large numbers of animals/group, and validated endpoints (e.g., Myers et al, 2008;Tyl, 2009). The dietary BPA multigeneration studies (under EPA and OECD testing guidelines and GLPs) in CD (SD) rats (Tyl et al, 2002) and CD-1 (Swiss) mice (Tyl et al, 2008c) Gray et al (2004), Goodman et al (2006), Willhite et al (2008, and others. The Tyl studies reported no systemic effects at or below 5 mg/kg/day (down to less than 1 μg/kg/day) and no reproductive/developmental effects at or below 50 mg/kg/day in either species.…”
mentioning
confidence: 99%
“…The relatively few regulatory testing guidelines of large multigeneration reproductive toxicology studies are under governmental guidelines and GLPs, with oral routes of administration, a larger number of groups (minimum 4), large numbers of animals/group, and validated endpoints (e.g., Myers et al, 2008;Tyl, 2009). The dietary BPA multigeneration studies (under EPA and OECD testing guidelines and GLPs) in CD (SD) rats (Tyl et al, 2002) and CD-1 (Swiss) mice (Tyl et al, 2008c) Gray et al (2004), Goodman et al (2006), Willhite et al (2008, and others. The Tyl studies reported no systemic effects at or below 5 mg/kg/day (down to less than 1 μg/kg/day) and no reproductive/developmental effects at or below 50 mg/kg/day in either species.…”
mentioning
confidence: 99%
“…In contrast, there are research studies that do not agree with the above conclusions and indicate that there is no immunologic, neurologic, genotoxic or carcinogenic risk for humans by oral ingestion of BPA (15).…”
Section: Human Health Effects From Bpa Dietary Intake Exposurementioning
confidence: 55%
“…thus beyond the controversial association of higher risk for disease in humans and the even more controversially discussed results of animal studies, the historical approach of toxicological risk assessment, including allometric scaling and pharmacologically based pharmacokinetic (PBPK) models with interspecies scaling, interaction with the eR, determination of actual human exposure, use of safety factors (NRC, 2000), etc., would not provide for an increased endocrine disruptive health risk for humans via exposure to BPA (Goodman et al, 2006;Chapin et al, 2008;Willhite et al, 2008;Goodman et al, 2009). the latter view is presently shared by all expert teams of national authorities involved in human risk assessment of BPA.…”
Section: The "Association" Issuementioning
confidence: 99%